Analisis Mekanisme Penyusunan Surat Pertanggungjawaban (SPJ) Perjalanan Dinas sebagai Bentuk Akuntabilitas Administrasi Keuangan - Rahima Ayu Zaharani; Herry Sutanto (Journal of Economics, Management, and Accounting, 2026)
This study is conducted based on the importance of preparing Official Travel Accountability Reports (SPJ) in accordance with administrative regulations to support accountable financial management. The need for a well-structured accountability system has become increasingly relevant in line with the growing demands for transparency and accountability in regional financial management. The study aims to examine in depth the mechanism for preparing SPJ documents for official travel at the Department of Industry and Trade of West Java Province. This research employs a descriptive qualitative approach with data collection through direct observation, interviews, and documentation. The findings indicate that the SPJ preparation mechanism is carried out in a structured and systematic manner through document preparation by the activity executor (PPTK), verification by the verifier, examination by the disbursement treasurer, further verification by the budget administration official (PPK-SKPD), and approval by the budget user (PA). Each stage functions as a distinct control point while remaining interconnected within an internal control system that ensures document validity and completeness. The mechanism not only serves an administrative purpose but also functions as an important instrument for maintaining financial accountability in local government. Therefore, the effectiveness of each stage becomes a determining factor in ensuring transparent and accountable financial administration.